Empowering education and society through digital literacy - Halim, Nurul Syafawani; Azmi, Sharina Salmi; Amzah, Rodhiah; Nik Mat, Nik Mahfuzah; Mohd Salim, Mohd Nur Fitri (Universiti Teknologi MARA, Negeri Sembilan, 2025)
In today’s digital environment, the ability to navigate and critically evaluate digital information has shifted from an optional skill to an essential requirement. Digital literacy encompasses the competencies needed to assess online content critically, understand digital ethics, and utilise digital tools responsibly. As digital technologies continue to reshape education, it is imperative that individuals develop these skills to remain relevant in an increasingly complex information landscape. This need is particularly pressing in an era marked by widespread misinformation and digital manipulation, where strong critical thinking and evaluative abilities are vital for making informed decisions. Therefore, fostering digital literacy is essential not only for enhancing teaching and learning but also for equipping individuals with workforce-relevant competencies, promoting equitable access to education, and preparing individuals to participate in a digitally interconnected society.